The Impact of Epithelial–Mesenchymal Transition and Metformin on Pancreatic Cancer Chemoresistance: A Pathway towards Individualized Therapy - Aiste Gulla; Urte Andriusaityte; Gabrielius Tomas Zdanys; Elena Babonaite; Kestutis Strupas; Helena Kelly (Medicina, 2022)
Globally, pancreatic ductal adenocarcinoma remains among the most aggressive forms of neoplastic diseases, having a dismal prognostic outcome. Recent findings elucidated that epithelial–mesenchymal transition (EMT) can play an important role in pancreatic tumorigenic processes, as it contributes to the manifestation of malignant proliferative masses, which impede adequate drug delivery. An organized literature search with PubMed, Scopus, Microsoft Academic and the Cochrane library was performed for articles published in English from 2011 to 2021 to review and summarize the latest updates and knowledge on the current understanding of EMT and its implications for tumorigenesis and chemoresistance. Furthermore, in the present paper, we investigate the recent findings on metformin as a possible neoadjuvant chemotherapy agent, which affects EMT progression and potentially provides superior oncological outcomes for PDAC patients. Our main conclusions indicate that selectively suppressing EMT in pancreatic cancer cells has a promising therapeutic utility by selectively targeting the chemotherapy-resistant sub-population of cancer stem cells, inhibiting tumor growth via EMT pathways and thereby improving remission in PDAC patients. Moreover, given that TGF-β1-driven EMT generates the migration of tumor-initiating cells by directly linking the acquisition of abnormal cellular motility with the maintenance of tumor initiating potency, the chemoprevention of TGF-β1-induced EMT may have promising clinical applications in the therapeutic management of PDAC outcomes.